Analisis Pengetahuan Akuntansi dan Pengalaman Usaha Terhadap Pengembangan Usaha serta Penggunaan Informasi Akuntansi Sebagai Variabel Intervening - Neni Marlina Br Purba; Ronald Wangdra (LPPM Universitas Putera Batam, 2023)
This research was conducted to find out the results of research on accounting knowledge and business experience on business development as well as the use of accounting information as an intervening variable carried out on micro business actors in Batam City. The population is all micro business actors in Batam City who are registered with the Office of Cooperatives and Micro Enterprises in Batam City. While the sample was randomly selected and calculated using the slovin formula as many as 87 respondents. Primary data is used and obtained by sharing the Google form. Data analysis using Outer Model tests (Outer Loading, composite reliability, Cronbach's alpha and AVE) and Inner Model (Multicollinearity, linearity, endogeneity, direct and indirect hypothesis tests, R sqare test) with the help of the SmartPLS4 application. The research results show that direct business experience and accounting knowledge have a significant effect on business development. Accounting knowledge and business experience directly have a significant effect on the use of accounting information. Meanwhile, the direct use of accounting information has no significant effect on business development. Indirectly, the use of accounting information does not become intervening between the independent variables on the dependent variable.